High performance mortar for ductile seismic-resistant unreinforced masonry systems. (10th June 2020) - Laghi, Vittoria; Palermo, Michele; Incerti, Andrea; Gasparini, Giada; Trombetti, Tomaso
Highlights: Unreinforced masonry (URM) systems although are typically not earthquake-resistant. A possible strategy is to increase the ductility of URM system through the mortar. The research program "ZERO" developed and tested a ductile mortar for URM systems. The results evidenced improved strength and ductility of the overall masonry system. Abstract: The paper presents the results of an experimental campaign aimed at assessing the structural performances of unreinforced masonry systems realized with a novel ductile mortar. The experimental campaign described in the paper is part of the research project "Zero Environmental Risks in Our buildings" (ZERO) whose broad objective is to develop a new class of construction materials and decorative products characterized by high environmental compatibility, i.e. Volatile Organic Compounds (VOC)-free, as well as superior performances in terms of both chemical and mechanical properties. Two mortar formulations, one for thin-joints and one for thick-joints, have been tested under flexural and compressive loads, and their performances compared with those of benchmark mortars available in the market. Masonry assemblies have been realized with different types of hollow clay blocks available in the market, including flat structural and non-structural blocks for thin joints and structural clay blocks for ordinary joints. The results of the experimental tests proved the effectiveness of the innovative ductile mortar in improving both shear strength and shear deformation capacities of unreinforced masonry assemblies.